Bottom-up innovations in natural hazard risk management in Austria. (January 2022) - Thaler, Thomas; Attems, Marie-Sophie; Fuchs, Sven
Abstract: Current procedures in risk management request new institutional innovations to effectively respond to observed dynamics. This paper aims to assess and explain institutional innovations in natural hazard risk management by analyzing examples of multi-functional protection schemes, which are distinctive to mainstream solutions. These multi-functional protection schemes combine several different functions (e.g. risk management strategy, sustainable land-use development, individual preparedness and well-being) that are concerned with mitigation systems in order to save space, time and possible arising costs. The paper uses a mixed method approach. The first step includes 14 qualitative standardized semi-structured interviews with key stakeholders connected to proposed transformative strategies in selected four study sites. As a second step, we conducted an explorative scenario analysis with key experts based on potential upscaling of bottom-up innovations to the mainstream natural hazard risk management in Austria. The results highlight that institutional innovations in risk management are dependent on bottom-up initiatives instead of top-down decisions. Consequently, these measures also need a larger risk acceptance among decision makers and the public. Innovations are based on individual interests and certain policy entrepreneurs at local level; however, national authorities act as 'gatekeepers' which allows innovation at local level. Based on these variables, three selected policy pathways were developed to show the tipping points necessary for policy transformation in Austria. Highlights: Natural hazard risk management is often organized in a traditional manner. There is a need for institutional innovations to respond to future challenges caused by a warmer climate and land use change. This paper aims to assess and explain institutional innovations in natural hazard risk management in Austria. Institutional innovations in risk management are dependent on bottom-up initiatives instead of top-down decisions. Bottom-up innovation in natural hazard risk management is mainly based on the solution of local problems.